Parallel worlds : the science of alternative universes and our future of the cosmos - Kaku, Michio (London : Penguin Books, 2006)
Sheds new light on discoveries that have revolutionized the field of cosmology and transformed understanding of the universe, offering an explanation of the multiverse M-theory and its implications in terms of the fate of our own universe.
pt. 1. The universe: Baby pictures of the universe -- The paradoxical universe -- The Big Bang -- Inflation and parallel universes. -- pt. 2. The multiverse: Dimensional portals and time travel -- Parallel quantum universes -- M-theory: the mother of all strings -- A designer universe? -- Searching for echoes from the eleventh dimension. -- pt. 3. Escape into hyperspace: The end of everything -- Escaping the universe -- Beyond the multiverse.
Originally published by Doubleday in 2005.
Includes bibliographical references : pages [403]-405) and index.
Keywords: Cosmology; Big bang theory; Superstring theories; Supergravity